THE STUDY OF CORR ELA TION OF B- COEFFICIENT WITH OTHER ADDITIV E PROPERTIES FOR CROTONIC ACID (Biological Sciences - PJSIR, 2001)
Viscosities  of crotonic acid solutions i n aqueous and aqueous butanol  mixtures (2%, 4%, 6%, v/v) were   measured at various concentrations I .Ox l Q·3 to 5.0x l 0·1 mol.dm ·3 at different tem peratures 35° to 50°C. Ion-ion and ion-solvent inter actions were studied i n terms of A and 8-coefficients of Jones-Dole equation. The negative val ues of B-coefficients increased with rise of temperatures led to the conclusion that crotonic acid in aqueous and aqueous butanol mixtures behaves as structure maker. Thermochemical data i n terms of activation parameters such as energy of activation (ETJ ), change i n free energy of activation (DG*) and change in entropy of activation (8S*) as a function of temperature, salt concentration and sol vent composition were also eval uated.